Polyandrous females benefit by producing sons that achieve high reproductive success in a competitive environment - Firman, Renée C. (The Royal Society, 2011)
Females of many taxa often copulate with multiple males and incite sperm competition. On the premise that males of high genetic quality are more successful in sperm competition, it has been suggested that females may benefit from polyandry by accruing ‘good genes’ for their offspring. Laboratory studies have shown that multiple mating can increase female fitness through enhanced embryo viability, and have exposed how polyandry influences the evolution of the ejaculate. However, such studies often do not allow for both female mate choice and male–male competition to operate simultaneously. Here, I took house mice (Mus domesticus) from selection lines that had been evolving with (polygamous) and without (monogamous) sperm competition for 16 generations and, by placing them in free-ranging enclosures for 11 weeks, forced them to compete for access to resources and mates. Parentage analyses revealed that female reproductive success was not influenced by selection history, but there was a significant paternity bias towards males from the polygamous selection lines. Therefore, I show that female house mice benefit from polyandry by producing sons that achieve increased fitness in a semi-natural environment.